Guillain-Barré Syndrome Outbreak in Peru 2019 Associated With Campylobacter jejuni Infection. Issue 2 (5th March 2021) - Ramos, Ana P.; Leonhard, Sonja E.; Halstead, Susan K.; Cuba, Mireya A.; Castañeda, Carlos C.; Dioses, Jose A.; Tipismana, Martin A.; Abanto, Jesus T.; Llanos, Alejandro; Gourlay, Dawn; Grogl, Max; Ramos, Mariana; et al.
Abstract : Objective: To identify the clinical phenotypes and infectious triggers in the 2019 Peruvian Guillain-Barré syndrome (GBS) outbreak. Methods: We prospectively collected clinical and neurophysiologic data of patients with GBS admitted to a tertiary hospital in Lima, Peru, between May and August 2019. Molecular, immunologic, and microbiological methods were used to identify causative infectious agents. Sera from 41 controls were compared with cases for antibodies to Campylobacter jejuni and gangliosides. Genomic analysis was performed on 4 C jejuni isolates. Results: The 49 included patients had a median age of 44 years (interquartile range [IQR] 30–54 years), and 28 (57%) were male. Thirty-two (65%) had symptoms of a preceding infection: 24 (49%) diarrhea and 13 (27%) upper respiratory tract infection. The median time between infectious to neurologic symptoms was 3 days (IQR 2–9 days). Eighty percent had a pure motor form of GBS, 21 (43%) had the axonal electrophysiologic subtype, and 18% the demyelinating subtype. Evidence of recent C jejuni infection was found in 28/43 (65%). No evidence of recent arbovirus infection was found. Twenty-three cases vs 11 controls (OR 3.3, confidence interval [CI] 95% 1.2–9.2, p < 0.01) had IgM and/or IgA antibodies against C jejuni . Anti-GM1:phosphatidylserine and/or anti-GT1a:GM1 heteromeric complex antibodies were strongly positive in cases (92.9% sensitivity and 68.3% specificity). Genomic analysis showed that the C jejuni strains were closely related and had the Asn51 polymorphism at cstII gene. Conclusions: Our study indicates that the 2019 Peruvian GBS outbreak was associated with C jejuni infection and that the C jejuni strains linked to GBS circulate widely in different parts of the world.